2022
DOI: 10.1039/d2nj04406d
|View full text |Cite
|
Sign up to set email alerts
|

The mineralization ability of a chloride-resistant γ-Cu2(OH)3Cl Fenton catalyst: effects of the cation type, salt concentration and organic pollutants

Abstract: A chloride-resistant heterogeneous Fenton catalyst γ-Cu2(OH)3Cl is used to mineralize aromatic organics (phenol, bisphenol A, salicylic acid and aniline) in saline solutions with different salts (MgCl2, CaCl2, NaCl and KCl) and concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…The latest research indicated g-Cu 2 (OH) 3 Cl possessed a superior chloride-resistant ability to effectively mineralize organics in high chloride solutions. 13,14 LDHs can couple with other metal-based or carbonaceous materials to form novel composites, which is a good alternative to enhance their catalytic performance in Fenton reactions. 5 Cubased LDHs and g-Cu 2 (OH) 3 Cl have similar layered structures and contain Cu-OH octahedra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest research indicated g-Cu 2 (OH) 3 Cl possessed a superior chloride-resistant ability to effectively mineralize organics in high chloride solutions. 13,14 LDHs can couple with other metal-based or carbonaceous materials to form novel composites, which is a good alternative to enhance their catalytic performance in Fenton reactions. 5 Cubased LDHs and g-Cu 2 (OH) 3 Cl have similar layered structures and contain Cu-OH octahedra.…”
Section: Introductionmentioning
confidence: 99%
“…The latest research indicated γ-Cu 2 (OH) 3 Cl possessed a superior chloride-resistant ability to effectively mineralize organics in high chloride solutions. 13,14…”
Section: Introductionmentioning
confidence: 99%